2017
DOI: 10.1515/intag-2016-0057
|View full text |Cite
|
Sign up to set email alerts
|

Methanogenic community composition in an organic waste mixture in an anaerobic bioreactor

Abstract: A b s t r a c t. The aim of the study was to elucidate the substantial relationship between the compositions of methanogen community that assembles in the anaerobic digester mass and link it to methane production activity. The results of the metagenomic studies were used to evaluate how the methanogen structure changes during an anaerobic digestion process under various waste retention times (21, 23, 25, 29, 33, 39, 47 and 61 days). Phylogenetically coherent populations of methanogens were assessed by 16S rRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…The differences found in methanogens biodiversity between biowaste and biogas residues result from the stage of anaerobic digestion. The composition of methanogens is in consistent with the results of Gryta et al (2017). At the beginning of the process, methanogens inoculum is added to the substrates in order to initialize methanogenesis and thus biogas production.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The differences found in methanogens biodiversity between biowaste and biogas residues result from the stage of anaerobic digestion. The composition of methanogens is in consistent with the results of Gryta et al (2017). At the beginning of the process, methanogens inoculum is added to the substrates in order to initialize methanogenesis and thus biogas production.…”
Section: Resultssupporting
confidence: 78%
“…Acetate is first oxidized to H 2 and CO 2 and subsequently converted to methane. The occurrence of Methanobrevibacter genus members is typical for fruit waste anaerobic digestion (Gryta et al 2017), as found in the biowaste examined.…”
Section: Resultsmentioning
confidence: 66%
“…5758 described by Karakashev et al (2006). What is more, the high ratio of Methanosaetaceae to Methanosarcinaceae indicated quite a low acetate threshold, growth rate, and yield susceptibility, as previously noted by Gryta et al (2017). On the other hand, it has been observed that Clostridium spp.…”
Section: Discussionmentioning
confidence: 53%
“…The DNA from different types of biomass was extracted using a FAST DNA Spin Kit for Feces (MPBiomedicals, Santa Ana, CA, USA) according to the protocol, as described previously by Gryta et al (2017). The amount of DNA was determined by a NanoDrop® 2000 spectrophotometer (Thermo Scientific™, Waltham, MA, USA).…”
Section: Metagenomic Analysis By Ngs Dna Isolationmentioning
confidence: 99%